The influence of light microclimate on the lipid profile and associated transcripts of photosynthetically active grape berry seeds - Garrido, Andreia; Conde, Artur; De Vos, Ric C. H.; Cunha, Ana (Frontiers in Plant Science, 2023)
Lipids and oils determine the quality and industrial value of grape seeds. Studies with legume seeds demonstrated the influence of light on lipid metabolism and its association with seed photosynthesis. Grape berry seeds are photosynthetically active till mature stage, but mostly during the green stage and veraison. The objective of this work was to compare the lipid profiles of seeds from white grape berries (cv. Alvarinho) growing at two contrasting light microclimates in the canopy (low and high light, LL and HL respectively), previously reported to have distinct photosynthetic competences. Berries were collected at three developmental stages (green, veraison and mature) and from both microclimates, and the seeds were analyzed for their lipid profiles in an untargeted manner using liquid chromatography coupled to high resolution mass spectrometry (LCMS). The seed lipid profiles differed greatly among berry developmental stages, and to a lesser extend between microclimates. The LL microclimate coincided with a higher relative levels of fatty acids specifically at mature stage, while the HL microclimate led to an up-regulation of ceramides at green stage and of triacylglycerols and glycerophospholipids at mature stage. The seed transcript levels of four key genes (VvACCase1, Vv∆9FAD, VvFAD6 and VvLOXO) involved in fatty acid metabolism were analyzed using real-time qPCR. The lipoxygenase gene (VvLOXO) was down- and up-regulated by HL, as compared to LL, in seeds at green and veraison stages, respectively. These results suggest that seed photosynthesis may play distinct roles during seed growth and development, possibly by fueling different lipid pathways: at green stage mainly towards the accumulation of membrane-bound lipid species that are essential for cell growth and maintenance of the photosynthetic machinery itself; and at veraison and mature stages mainly towards storage lipids that contribute to the final quality of the grape seeds.